1985
DOI: 10.1111/j.1432-1033.1985.tb08712.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of human IgG subclasses in solution

Abstract: The structure of six human myeloma proteins: IgGl(Bal), IgG2(Klu), IgG3(Bak), IgG3(Het), IgG4(Kov) and IgG4(Pol), was studied in solution using small-angle X-ray scattering and hydrodynamic methods. For IgGl (Bal) and IgG3(Het) the experimental data, including radius of gyration (R",), radii of gyration of the cross-section (Rql, RqJ, intrinsic viscosity [q], sedimentation coefficient SO^^,^) and molecular mass, were interpreted in terms of structural models based on the Fab and Fc conformations, observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…The use of three NaCl concentrations examined potential electrostatic effects on the IgG1 structure, whereas heavy water is a known promoter of protein self-association. By comparison, earlier scattering studies on human IgG1 reported few scattering and ultracentrifugation runs or were performed in nonphysiological buffer conditions (28,38,39,(47)(48)(49). Both IgG1 6a and IgG1 19a showed similar experimental R g and R xs values and the same overall length of 16 nm ( Table 1 6.3-6.4 S, which were indistinguishable within error.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The use of three NaCl concentrations examined potential electrostatic effects on the IgG1 structure, whereas heavy water is a known promoter of protein self-association. By comparison, earlier scattering studies on human IgG1 reported few scattering and ultracentrifugation runs or were performed in nonphysiological buffer conditions (28,38,39,(47)(48)(49). Both IgG1 6a and IgG1 19a showed similar experimental R g and R xs values and the same overall length of 16 nm ( Table 1 6.3-6.4 S, which were indistinguishable within error.…”
Section: Discussionmentioning
confidence: 81%
“…4). A major monomer peak was observed at s 20 (38,39,40). Both IgG1 6a and IgG1 19a were predominantly monomeric in solution and were accompanied by a minor dimer peak.…”
Section: Resultsmentioning
confidence: 87%
“…79 Even though IgG possess a unique quaternary structure, 87 the binding ratio on NTs remained comparable with other studied proteins. With denaturated IgG, however, the three dimensional conformation was destroyed and, consequentially, the binding was reduced, with the trend of binding with regard to the NTs diameters remaining unchanged.…”
mentioning
confidence: 99%
“…In Table I1 these results are shown along with the experimental ones. 12 We can see that differences between both theoretical treatments are negligible in the rigid limit. Differences in the flexible limit are due to the small but finite probability of overlapping between beads that is allowed by the Lennard-Jones potential and that is not considered in the rigidbody approximation.…”
Section: Overall Propertiesmentioning
confidence: 93%